PENGARUH SISTEM MANAJEMEN DAN KOMPETENSI MANAJERIAL KEPALA MADRASAH TERHADAP PRESTASI BELAJAR PESERTA DIDIK - Irmawanti Kasim (Universitas Muhammadiyah Surakarta, 2020)
This research aims to analyze and examine the influence of management system and principal’s managerial competence to students’ achievements at Madrasah Ibtidaiyah in Bulukumpa District of Bulukumba Regency, South Sulawesi. This research is a quantitative study with the ex post facto method. Respondents in this study as many as 75 teachers were taken in total at Madrasah Ibtidaiyah in Bulukumpa District. The data collection techniques used are questionnaire and documentation, then the analysis used to examine the hypothesis is inferential statistics through regression analysis. The results of this study show that partially, the management system and principal’s managerial competence positive influence to students’ achievement. Simultaneously, management system and principal’s managerial competencies also have significant effect on students’ achievement. This indicates that the low level of students’ achievement, there is influence of management system and managerial competence applied by the headmaster at Madrasah Ibtidaiyah in Bulukumpa District of Bulukumba Regency.Keywords: Management system, principal’s managerial competence, students’ achievement